COMPARISON OF SOMATIC EMBRYO FORMATION IN OCIMUM BASILICUM L., OCIMUM SANCTUM L. & OCIMUM GRATISSIMUM L. - REBECCA MATHEW; DEEPA SANKAR P (International Journal of Pharma and Bio Sciences, 2011)
Cotyledonary leaves of Ocimum species viz., Ocimum basilicum L., Ocimum sanctum L. & Ocimum gratissimum L. were used for comparative studies on somatic embryogenesis. Murashige and Skoog (MS) medium with 2,4-Dichlorophenoxyacetic acid (2,4-D) and benzyladenine (BA) was used to initiate callus. MS with 1.0 mg l-1 2,4-D + 0.5 mg l-1 BA was found suitable for the development of callus with maximum weight and lesser days to induction for O. basilicum and O. sanctum whereas MS with 0.5 mg l-1 2,4-D + 0.5 mg l-1 BA initiated callus of maximum weight with high % of response and lesser days to induction for O. gratissimum. High % of response to callus induction was found in MS with1.5 mg l-1 2,4-D + 0.5 mg l-1 BA for O. basilicum and O. sanctum. Differentiation into globular stage of somatic embryos was observed in all cultures but with variation in duration, % response and embryo colour, on transfer of sub-cultured callus to MS media containing different concentrations and combinations of BA, Kinetin (KIN) & Indole Acetic Acid (IAA). Maximum differentiation into globular shaped somatic embryos was observed in all concentration ranges of KIN with or without IAA and in BA (2.0, 3.0 mg l-1) which had coconut water (CW) as an additional supplement.